HOW EFFECTIVE IS SIMULATION-BASED EDUCATION FOR IMPROVING THE NURSES’ KNOWLEDGE ON PEDIATRIC IV INSERTION: A SYNTHESIS FROM AWAL BROS HOSPITAL GROUP IN INDONESIA - Retno Dewi Sulistyowati; Adang Bachtiar (Proceedings of the International Conference on Applied Science and Health, 2019)
Background: Simulation-based nursing education has been growing rapidly and becomes one of the most popular teaching methods for improving patient safety and patient care. One of the difficult Nursing skills to achieve is IV insertion. Due to the high complaints in the number of IV insertion attempts in the paediatric patients, the Nursing Corporate of Awal Bros HospitalGroup organized an educational program emphasizing the team training, clinical decisionmaking and communication skills. These were the first internal education sessions using live rabbits and mannequins. This study aimed to evaluate the attitude of the participants, the selfconfidence level and their change in the knowledge on clinical performance in Paediatric IV Insertion after attending the educational program. Methods: The training and education sessions were conducted at Awal Bros Hospitals in Bekasi Barat and Tangerang during March and April 2019. The participants included a total of 52 Nurses. Pre- and Post-tests consisting of 20 multiple choice questions were administered to the participant before and after the 3-day simulation-based training workshop in Bekasi Barat and after the 2-day simulationbased training workshop in Tangerang. The workshop also utilized rabbits for the participants to practice their hands-on skills. Results: A total of 52 Nurses working in different Nursing units were enrolled. The mean pre-test and post-test scores were 43.81 and 87.52 respectively. In the Statistics Test table, the value of Asymp. Sig (2-tailed) was 0,000. Because the value of sig 0,000 < 0.05 was according to the statistical tests we used, then there are significant differences between before training and after training. Conclusions: Participants had positive attitude toward this new training program. They stated that this technique was more exciting and effective compared to the “traditional” techniques such as lecture, power point presentations or Q&A that they attended. Significant improvement of the knowledge on clinical performance in Nurses participating in these training and education session was observed after the participation in this simulation-based educational program. Many expressed their higher selfconfidence in doing IV insertion to the future patients, especially babies and children. More simulationbased education using pre- and post-tests are recommended. Keywords: Education, Nursing, IV Insertion